Analisis Bentuk Estetik pada Properti Visual Ritual Obong Masyarakat Kalang Kabupaten Kendal - Abdul Aziz; Eko Sugiarto; Muh Fakhrihun Naam (Catharsis, 2023)
The obong ritual is a death ritual carried out by the kalang community as a means of respecting the spirits of deceased ancestors. This ritual is a local wisdom in Kendal Regency. However, many people of kalang descent have abandoned obong rituals, so there is a need for cultural socialization media so that these rituals are not eroded by the times. This research aims to analyze the aesthetic form, symbolic meaning, and role of the obong ritual as a medium for cultural socialization. The research method used is a qualitative approach. Data was taken using in-depth interviews, documentation and observation. The research was conducted in Tratemulyo Village, Weleri District, Kendal Regency. The uniqueness of this research location is that the majority of the kalang people in Tratemulyo Village are actually Muslim, but still practice and carry out ceremonies of respect for ancestral spirits in the form of obong rituals. The research results show that the aesthetic form of the visual properties used in the obong ritual contains deep symbolism. It is not just decoration, but also summarizes the values and traditions that have been passed down from generation to generation. The symbolic meaning of offerings in the obong ritual never experiences a shift in meaning, because the meaning is passed down from generation to generation by the kalang shaman.